Can differences in the type, nature or amount of polysubstance use explain the increased risk of non-fatal overdose among psychologically distressed people who inject drugs? - Betts, K.; McIlwraith, F.; Dietze, P.; Whittaker, E.; Burns, L.; Cogger, S.; Alati, Rosa (Elsevier Ireland Ltd, 2015)
© 2015 Elsevier Ireland Ltd. Background: This study investigates whether the type, nature or amount of polysubstance use can explain the increased risk of non-fatal overdose among people who inject drugs with severe psychological distress. Methods: Data came from three years (2011-2013) of the Illicit Drug Reporting System (IDRS), an annual sentinel sample of injecting drug users across Australia (. n=. 2673). Structural Equation Modelling (SEM) was used on 14 drug types to construct five latent factors, each representing a type of polysubstance use. Tests of measurement invariance were carried out to determine if polysubstance use profiles differed between those with and without severe psychological distress. Next, we regressed non-fatal overdose on the polysubstance use factors with differences in the relationships tested between groups. Findings: Among those with severe psychological distress a polysubstance use profile characterised by heroin, oxycodone, crystal methamphetamine and cocaine use was associated with greater risk of non-fatal overdose. Among those without severe psychological distress, two polysubstance use profiles, largely characterised by opioid substitution therapies and prescription drugs, were protective against non-fatal overdose. Conclusion: The types of polysubstance use profiles did not differ between people who inject drugs with and without severe psychological distress. However, the nature of use of one particular polysubstance profile placed the former group at a strongly increased risk of non-fatal overdose, while the nature of polysubstance use involving opioid substitution therapies was protective only among the latter group. The findings identify polysubstance use profiles of importance to drug-related harms among individuals with psychological problems.